Asian slaves in colonial Mexico from Chinos to Indians - Seijas, Tatiana (Cambridge Latin American studies, 2015)
"During the late sixteenth and seventeenth centuries, countless slaves from culturally diverse communities in the Indian subcontinent and Southeast Asia journeyed to Mexico on the ships of the Manila Galleon. Upon arrival in Mexico, they were grouped together and categorized as chinos. In time, chinos came to be treated under the law as Indians (the term for all native people of Spain's colonies) and became indigenous vassals of the Spanish crown after 1672. The implications of this legal change were enormous: as Indians, rather than chinos, they could no longer be held as slaves. By tracking these individuals' complex journey from the bondage of the Manila slave market to the freedom of Mexico City streets, Tatiana Seijas challenges commonly held assumptions about the uniformity of the slave experience in the Americas and shows that the history of coerced labor is necessarily connected to colonial expansion and forced global migration"--